1998
DOI: 10.1038/sj.onc.1201534
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the pRB-family proteins with factors containing paired-like homeodomains

Abstract: The speci®c loss of pRB or p107 together with p130 disrupts the normal development of only a very limited spectrum of tissues. These developmental defects have been attributed primarily to deregulation of E2F activity and consequent uncontrolled proliferation. We hypothesized, however, that the tissue-speci®c nature of these defects may also re¯ect deregulation of pRB-family associated factors that are speci®cally involved in determining cell fate. We report here that the pRBfamily members interact with transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…This hypothesis is also supported by studies that show a direct interaction between pRb and factors containing paired-like homeodomains (Wiggan et al, 1998). Interestingly, Eberhard and Busslinger (1999) have demonstrated the direct interaction between Pax 5 and pRb both in vitro and in vivo and it has been reported that pRb interacts with Pax 2 (Yuan et al, 2002).…”
Section: Introductionsupporting
confidence: 58%
“…This hypothesis is also supported by studies that show a direct interaction between pRb and factors containing paired-like homeodomains (Wiggan et al, 1998). Interestingly, Eberhard and Busslinger (1999) have demonstrated the direct interaction between Pax 5 and pRb both in vitro and in vivo and it has been reported that pRb interacts with Pax 2 (Yuan et al, 2002).…”
Section: Introductionsupporting
confidence: 58%
“…For example, since pRB represses the activity of Pax3 (Wiggan et al, 1998), we predicted that Pax3-dependent induction of a MET in the pRB-positive human osteosarcoma, U2-OS, would be retarded. As Figure 4a and b illustrates, a small but significant reduction in the size of U2-OS cells occurs following expression of Pax3.…”
Section: Pax3/fkhr Is a More Potent Activator Of Met Than Pax3mentioning
confidence: 99%
“…Pax3 activity is further regulated through binding of other nuclear factors. For example, both Daxx and pRB (Wiggan et al, 1998) associate with Pax3, repressing Pax3-dependent transcription in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the activity of the fusion protein is strongly in¯uenced by cell background, either due to lack of an appropriate coactivator in ®broblasts or lack of a repressing activity in myoblasts. Interestingly, two proteins have recently been identi®ed that can repress the activity of Pax3 but not PAX3/FKHR through direct interaction with the paired-type homeodomain, namely pRb and hDaxx Wiggan et al, 1998).…”
Section: Discussionmentioning
confidence: 99%